A Mammary Organoid Model to Study Branching Morphogenesis - Caruso, Marika; Huang, Sjanie; Mourao, Larissa; Scheele, Colinda L. G. J. (Frontiers in Physiology, 2022)
Branching morphogenesis is the process that gives rise to branched structures in several organs, such as the lung, the kidney and the mammary gland. Although morphologically well described, the exact mechanisms driving branch elongation and bifurcation are still poorly understood. Signaling cues from the stroma and extra-cellular matrix composition have an important role in driving branching morphogenesis. Organoid models derived from primary mammary epithelial cells have emerged as a powerful tool to gain insight into branching morphogenesis of the mammary gland. However, current available mammary organoid culture protocols result in morphologically simple structures which do not resemble the complex branched structure of the in vivo mammary gland. Supplementation of growth factors to mammary organoids cultured in basement membrane extract or collagen I were shown to induce bud formation and elongation, but are not sufficient to drive true branching events. Here, we present an improved culture approach based on 3D primary epithelial cell culture to develop branched organoids with a complex morphology. Using alternated addition of fibroblast growth factor 2 and epidermal growth factor in a basement membrane extract matrix enriched with collagen type I fibers, we obtain complex mammary organoid structures with primary, secondary and tertiary branches over a period of 15-20 days. Mammary organoid structures grow > 1 mm in size and show an elongated and branched shape which resembles in vivo mammary gland morphology. This novel branched mammary organoid model offers many possibilities to study the mechanisms of branching in the developing mammary gland.